Economic policy uncertainty of China and investment opportunities: A tale of ASEAN stock markets - Hassanudin Bin Mohd Thas Thaker; Mohamed Asmy Mohd Thas Thaker; Muhammad Rizky Prima Sakti; Imtiaz Sifat; Anwar Allah Pitchay; Hafezali Iqbal Hussain (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The purpose of this paper is to examine the effect of economic policy uncertainty (EPU) of China on investment opportunities in five ASEAN economies. Design/methodology/approach - This paper employs advanced empirical approaches, such as Multivariate DCC-GARCH and Continuous Wavelet Transform (CWT) to test the research objective. The period of analysis involved monthly data from 2003 until 2019. Findings - This paper provides evidence where the Malaysian stock market to be the least exposed to risks emanating from Chinese EPU, followed by Singapore, the Philippines, Thailand and Indonesia. Results for investment opportunities based on time horizon suggest, for a short-term holding period, investors are better off investing in Singapore and Indonesia, while, for medium-term holding periods, all ASEAN markets appear lucrative except for the Philippines. Practical implications - From a managerial perspective, the outcome or findings of this study are expected to aid the retail and institutional investors in designing better strategies on diversifying a stock portfolio with different holding periods. Originality/value -Theoretically, the findings of this study contribute fresh insights into an emerging strand of literature focusing on the transmission of regional policy. Methodologically as well, this study is a novel venture to the best of authors' knowledge.
Keywords: E0; E2; E5; F1; 330; Economic policy uncertainty; Investment; ASEAN markets; Stock markets; GARCH; Wavelet